COMPETENCE IMPROVEMENT OF OFFICE ADMINISTRATION TEACHERS THROUGH COMMERCIALIZATION OF PRODUCTIVE, CREATIVE, AND ENTREPRENEURS SUBJECT IN THE INDUSTRIAL REVOLUTION 4.0 - Heny Kusdiyanti; Mokhammad Nurruddin Zanky; Andy Prasetyo Wati; Indra Febrianto; Robby Wijaya (Universitas Islam Raden Rahmat Malang, 2019)
There are so many effort that have been done by the government to increase the contribution of the educational sector to support achievement of Industrial Revolution 4.0 in Indonesia. Teacher competence become one of the important thing in the educatioal improvement contribution. This study purposed to build the fundamental stategy for competence improvement model on administration’s teacher toward Industrial Revolution 4.0. This research done by training and data collection techniques used in this study are documentation, questionnaires, interviews, and test to responden. The result of this research are first, 76% of teachers understood the criteria for office administration programs that were able to face challenges in the industrial revolution era 4.0. In this case, it is able to mention a digital-based office administration program to answer the needs of industry 4.0 in the form of services. Secondly, 79% of teachers know the output of office administration programs from productive, creative and entrepreneurial (PKK) subjects that can be commercialized, including: typing services and event organizers. Based on the result it can be conclude that 2. This program is able to foster entrepreneurship (entrepreneurship) among the Office Administration Teachers in SMK 1 Boyolangu. 5. This program provides insight and provision for Tulungagung Regency Office Administration teachers who are able to provide guidance for students to live independently and skillfully now and in the future.